Energetic mixing of anti-SNAP25 on lipid monolayers: degree of saturation of C18 fatty acids - Gew, Lai Ti *; Misni Misran, (J. Wiley, 2016)
In our study, various mixtures of C18 fatty acids with different degrees of saturation in their hydrocarbon chain, namely stearic acid (SA), oleic acid (L1), linoleic acid (L2), and linolenic acid (L3), and a polyclonal antibody, anti-synaptosome-associated protein of 25 kDa (SNAP25) (AS25), have been investigated using the Langmuir–Blodgett (LB) technique accompanied by atomic force microscopy (AFM) imaging. The cis-double bonds in unsaturated lipids (L1, L2, and L3) have kinks in their molecular conformation and thus could not pack as tightly and uniformly as SA. The bends and kinks in the molecular structure may interfere with the packing of the lipid monolayer which will promote fluidity as shown in the analyzed compressibility modulus (Cs−1) data. The negative values of Gibbs free energy of mixing (ΔGmix) of C18 fatty acids/AS25 confirm the spontaneity interaction of AS25 molecules on the monolayers. The amount of AS25 incorporated into the monolayer strongly affected the thermodynamic properties of the lipid monolayers. AFM surface roughness analyses also indicate that AS25 molecules are strongly bounded on the surface membrane as predicted by the obtained energetic data. In comparison to all C18 fatty acids studied, the strongest intermolecular interaction is observed in L1 at the investigated ranges. In particular, at mole ratio of 26:1, the most negative ΔGmix is observed at L1. Thus, we can draw the conclusion that AS25 is best mixed with L1. This L1/AS25 ratio mimicking a half bilayer membrane serves as a very useful reference in preparing fatty-acid nanoimmunoliposomes as the targeted drug-delivery vehicles for cancer therapy